Analysis of Changes in Temporal Spatial Land Use, Vegetation, and Built-up Land in Grobogan Regency in 2019-2023 - Setiyaningsih, Diyah Ayu; Priyono, Kuswaji Dwi; Jumadi, Jumadi (International Journal for Disaster and Development Interface, 2025)
Along with the increasing population in Grobogan Regency, the need for sufficient clothing and boards will increase. The Grobogan area is in a karst area with the agricultural and blasting sectors contributing the biggest sources of GRDP. Agriculture is dominated by dry farming. The area of forest land (vegetation is the second largest in Central Java. The study aimed to determine the dynamics of changes that occur in land cover (agricultural areas, vacant land, built-up areas, vegetation, and water bodies), focusing on built-up areas and vegetation. Data processing uses the help of sentinel imagery for the period 2019-2023 which is then processed using the maximum likelihood method which is then tested for accuracy to match the actual conditions on the ground Vegetation (forest) The second biggest change is the conversion to agricultural land. This is also marked by areas the area found which is indicated as an increasing settlement.